2011
DOI: 10.1021/jo1022926
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Synthesis of All Stereoisomers of a 2,3-Unsaturated C-Glycoside Scaffold

Abstract: All stereoisomers of a highly functionalized 2,3-unsaturated C-glycoside can be accessed in 10-100 g quantities from readily available starting materials and reagents in 3-7 steps. These chiral scaffolds contain three stereogenic centers along with orthogonally protected functional groups for downstream reactivity.Due to their synthetic versatility and high level of stereochemical diversity carbohydrates have served as useful starting points for generating molecular diversity. 1 Carbohydratederived glycals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…This ratio is identical to that reported in a related C-glycolsylation reaction of this type. 47 We found that cis - and trans - isomers of 12a and 12b were readily separated by flash chromatography to give the stereochemically pure products. The relative stereochemistry of both isomers was established by NOESY experiments and by single crystal X-ray structures of 4-nitrophenyl ester derivatives (see Figure 3 and SI).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This ratio is identical to that reported in a related C-glycolsylation reaction of this type. 47 We found that cis - and trans - isomers of 12a and 12b were readily separated by flash chromatography to give the stereochemically pure products. The relative stereochemistry of both isomers was established by NOESY experiments and by single crystal X-ray structures of 4-nitrophenyl ester derivatives (see Figure 3 and SI).…”
Section: Resultsmentioning
confidence: 88%
“…We therefore pursued the alternative route to these intermediates that installed the desired stereochemistry and ester moiety in one step via a Ferrier-type rearrangement using a silylketene acetal. 4547 The stereochemical outcome of this reaction has previously been shown to be highly dependent on the conditions employed. 49 We developed conditions for this transformation that provided a 2:1 mixture of cis - and trans -fused substituted dihydropyrans 12a (in 72% yield) and 12b (in 70% yield).…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of pyran fragments 1 and 2 initiated with C-glycoside 6 (Scheme 1), which itself was derived from tri-O-acetyl D-and L-glycals according to methods previously developed in our laboratory (31). Methylation of 6 with Meerwein's reagent in the presence of Proton Sponge gave rise to the corresponding methyl ether in 69-94% yield, which in turn was hydrogenated under standard conditions (Pd/C, MeOH, H 2 ) to afford pyrans 7 in 94-100% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Marcaurelle et al 44 investigated the reaction of glucal 1 with ketene acetal 112 under various conditions, and found the reaction to be best carried out in the presence of TMSOTf in dichloromethane, yielding 73% of a 1:1.5 mixture of 108, favouring the β-anomer (Scheme 51).…”
Section: Scheme 50mentioning
confidence: 99%